Security management in mobile cloud computing - Munir, Kashif, 1976- (Information Science Reference, 2017)
"This book explores the difficulties and challenges of securing user data and information on mobile cloud platforms, investigating a variety of protocols and architectures that can be used to design, create, and develop security mechanisms"--Resumé vydavatele
Keywords: cloud computing; počítačové sítě; zabezpečení počítačových sítí; informační bezpečnost; computer networks; computer network security; information security; kolektivní monografie; elektronické knihy; collective monographs; electronic books